MAGNESIUM DEFICIENCY AND CARDIOVASCULAR DISEASES: TIME TO ACT - E. I. Trisvetova (Столичная издательская компания, 2015)
Progression of cardiovascular disease is often caused by a deficiency of magnesium in the human body. Magnesium belongs to the necessary vital macronutrients providing many physiological and pathological reactions and is involved in the constructive, energy, electrolyte metabolism. Correction of magnesium deficiency is realized using magnesium-containing drugs, for example magnesium orotate, having pleiotropic effects due to independent metabolic activity of orotic acid.